The extinctive prescription of the cause of action of the tax administration in the proceeding of collecting a tax debt: is legislative decree 1421 unconstitutional? - Durán Rojo, Luis (2019)
After Legislative Decree 1113 came into force, the discussion regarding the constitutionality of the extinctive prescription of the cause of action for the tax administration in the proceeding of collecting a tax debt arose. Such debate originated because the prescription period began running before the legislative decree came into force. In this article the authors explore constitutional foundation of extinctive prescription as well as they analyze the prescription of the cause of action for the tax administration collect a tax debt. faculty of collecting tax debts. Also, the authors examine the application over time of Legislative Decree 1113. Finally, they propose a proportionality test of the constitutional values in conflict.